2017
DOI: 10.1002/chem.201702615
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Binding to Protonated Heme in the Gas Phase, an Intermediate Between Ferric and Ferrous Heme

Abstract: With a view to characterizing the influence of the electronic structure of the Fe atom on the nature of its bond with dioxygen (O ) in heme compounds, a study of the UV/Vis action spectra and binding energies of heme-O molecules has been undertaken in the gas phase. The binding reaction of protonated ferrous heme [Fe -hemeH] with O has been studied in the gas phase by determining the equilibrium of complexed [Fe -hemeH(O )] with uncomplexed protonated heme in an ion trap at controlled temperatures. The binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…We first showed that, as opposed to the end-on configuration of FeP−O 2 , MnP−O 2 prefers the side-on configuration. Our theoretical results predict a side-on quartet GS, in agreement with an early prediction of Basolo et al based on IR and EPR 17,19 and a more recent work of Gallagher et al 20 A detailed analysis of the GS wave function revealed a strong charge transfer between MnP and O 2 , leading to an assignment of O 2 somewhere 21,47 Our theoretical results are in perfect agreement with the experimental data, with errors less than 2 kcal/mol. Both the experimental and calculated data clearly indicate that O 2 binds more strongly by 4-6 kcal mol −1 to manganese porphyrin than to the corresponding ferrous porphyrin.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We first showed that, as opposed to the end-on configuration of FeP−O 2 , MnP−O 2 prefers the side-on configuration. Our theoretical results predict a side-on quartet GS, in agreement with an early prediction of Basolo et al based on IR and EPR 17,19 and a more recent work of Gallagher et al 20 A detailed analysis of the GS wave function revealed a strong charge transfer between MnP and O 2 , leading to an assignment of O 2 somewhere 21,47 Our theoretical results are in perfect agreement with the experimental data, with errors less than 2 kcal/mol. Both the experimental and calculated data clearly indicate that O 2 binds more strongly by 4-6 kcal mol −1 to manganese porphyrin than to the corresponding ferrous porphyrin.…”
Section: Resultssupporting
confidence: 90%
“…Consequently, the binding enthalpy in [FehemeH] + -O 2 is reduced by 4.3 kcal mol −1 as compared to the neutral porphyrin. We finally note that experiments 47 and our calculations both predict a small standard binding enthalpy of O 2 to [FehemeH] + (4-5 kcal mol −1 ).…”
Section: Comparison To Experimentssupporting
confidence: 57%
See 2 more Smart Citations
“…While solution measurements hardly access the observation of 5C hemes because of the blocking ligation to H2O (or the solvent), only gas phase measurements [7][8][9][10][11][12] render the sole or sequential addition of ligands in axial position to heme rather simple, by physically separating the ligation events and avoiding the spurious ligation by H2O (or the solvent). Following our recent studies on the binding of small ligands to ferric heme 11 and protonated heme 12 in a cold, temperature controlled, ion trap, we herein use the same approach with the presence of N- Indeed, the Fe III atom in the high spin state S=5/2 inflates due to electron repulsion and pops out of the porphyrin cage.…”
Section: Introductionmentioning
confidence: 99%